ENGLISH-SPEAKING COUNTRIES AND THEIR GLOBAL INFLUENCE - Nurmatova Mubina Jaxongirovna (TADQIQOTLAR, 2025)
Abstract This article examines the multifaceted influence of English-speaking countries in the global arena. Focusing on historical roots, economic dominance, political power, cultural impact, and the spread of English as a global language, it provides a comprehensive overview of how nations such as the United States, United Kingdom, Canada, Australia, New Zealand, and Ireland shape global developments. The paper also explores challenges related to linguistic imperialism and the need to balance global communication with cultural and linguistic diversity.